Pengembangan Media Smart Box berbasis Science Environment Technology Society (SETS) dalam Pembelajaran IPA Sekolah Dasar - Tina Saofah; Din Azwar Uswatun; Astri Sutisnawati (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to describe the feasibility and effectiveness of smart box media in learning science elementary school students. This research is a type of Research and Development (R&D) with Borg and Gall design. Researchers use different types of methods to collect data, such as observation, interviews, questionnaires, documentation, and tests. The researchers used one group pretest-posttest experiment design. Experiments were conducted to test the effectiveness of smart box media in improving cognitive abilities in science learning. The results obtained from the needs analysis that has been done, using student response questionnaire, questionnaire practitioner / teacher, and questionnaire validation of experts can be concluded that the development of smart box media is getting a very decent category with the acquisition of value of 89% of the results of expert validation and 98% of the results of validation of practitioners. Then from the questionnaire the student's response was obtained by 90%. Analysis of the learning outcomes of the respondents became the subject of research, obtaining a score on the pretest 54 increased to 81 on the posttest, with an average value of 0.592 or 59% which is interpreted as moderate and quite effective. It can be concluded that the sets-based smart box media is included in the category of very feasible and can be used as auxiliary media in Learning Natural Sciences (IPA). Further research is needed in order to design learning process activities using sets-based smart box media in science learning in elementary schools.